Combining Z-Score and Maternal Copy Number Variation Analysis Increases the Positive Rate and Accuracy in Non-Invasive Prenatal Testing - Chen, Liheng; Wang, Lihong; Hu, Zhipeng; Tao, Yilun; Song, Wenxia; An, Yu; Li, Xiaoze (Frontiers in Genetics, 2022)
Objective: To evaluate positive rate and accuracy of non-invasive prenatal testing (NIPT) combining Z-score and maternal copy number variation (CNV) analysis. Methods: This prospective study included 61525 pregnancies to determine the correlation between Z-scores and positive predictive value (PPV) in NIPT, and 3184 pregnancies to perform maternal CNVs analysis. Logistic regression analysis and receiver operating characteristic (ROC) curves analysis were applied to associate Z-scores with PPV. And the maternal CNVs were classified according to the technical standard for the interpretation of ACMG. Prenatal diagnosis and/or following-up after birth were applied to verify the results of NIPT-positive. Results: Of the 3184 pregnant women, 22 pregnancies were positive for outlier Z-scores, suggesting fetal aneuploidy, while 12 of 22 were true positive based on prenatal diagnosis (PPV = 54.5%). Additionally, 18 carried maternal pathogenic or likely pathogenic CNVs (> 0.5 Mbp) through maternal CNV analysis. Prenatal diagnosis then revealed that 7 out of 11 fetuses carried the same CNVs as the mother. Two male fetuses were suspected of having the same condition, despite not being prenatally diagnosed, because biochemical indicators were abnormal and the CNV-associated clinical phenotypes appeared postnatally. Logistic regression analyses and ROC curves of the NIPT-positive of the 61525 pregnancies revealed that Z-scores of chromosomes 21 and 18 were significantly associated with PPV at 3 ≤ Z ≤ 40. Relationship trends were drawn using S-curves. Three pregnant women exhibited maternal aneuploidy at Z > 40. A score of Z < -3 indicated that fetuses might carry microdeletions instead of monosomy. Sex chromosome trisomy had significantly higher PPV than monosomy. Conclusions: The positive rate of the NIPT screening model combining Z-score and maternal CNV analysis increased from 6.91‰ (22/3184) to 12.56‰ (40/3184). True positives also increased from 12 to 21 pregnancies. Furthermore, we found a positive correlation between Z-score and PPV in a certain range. We can conclude that our model improves the positive rate and accuracy of NIPT in aneuploidy and CNVs without increasing testing costs. This method provides early warning of inherited pathogenic CNVs to the next generation.